Application of Single-Port Laparoscopic Surgery in Myomectomy - Jiang, Lili; Tong, Deming; Li, Yan; Liu, Qifang; Liu, Kuiran (Frontiers in Oncology, 2021)
Research question The use of a power morcellator in laparoscopic myomectomy is a controversial topic. The application of single-port laparoscopy solves this problem, but its safety, efficacy and prognosis are also challenges. The purpose of this study was to compare the clinical application of single-port laparoscopy and traditional three-port laparoscopy in myomectomy. Design This is a retrospective review of a total of 120 patients who underwent single-port laparoscopic myomectomy (n=60) or traditional three-port laparoscopic myomectomy (n=60), performed between January 2019 to December 2020. The operation time, intraoperative blood loss, specimen removal time, hemoglobin change after operation, postoperative ambulation time, first exhaust time after surgery, the length of hospital stay, pain score on the day, the first day after operation and the satisfaction of abdominal wall scar were evaluated for the surgical outcomes. Results Compared with the traditional three-port laparoscopic group, the specimen removal time, postoperative ambulation time, first exhaust time after surgery, the length of hospital stay were all shorter, the satisfaction of abdominal wall scar were higher in single-port laparoscopic group. The duration of surgery was longer in single-port laparoscopic group significantly. The differences were statistically significant(P<0.05). The intraoperative blood loss, hemoglobin change after operation, pain score on the day of operation and the first day after operation of the two groups had no differences(P>0.05). Conclusions The clinical effect of single-port laparoscopic myomectomy is satisfactory and can be popularized in clinic.